Efektifitas Rebusan Daun Babadotan dan Kombinasinya dengan Pregabalin sebagai Anti Nyeri Neuropatik serta Uji Toksisitas Akutnya - Yedy Purwandi Sukmawan; Hendy Suhendy; Maritsa Nurfatwa (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Neuropathic pain is a condition that is difficult to treated and impaired quality of life. The objective of the study was to determine the anti-neuropathic pain effectivity of Ageratum conyzoides aqueous extract and the acute toxicity study. We had 7 groups (normal, negative, pregabalin, ageratum. conyzoides-I (AC-I) 50mg/kg BW, A. conyzoides-II (AC-II) 100mg/kg BW, combination of pregabalin and AC-II), combination of AC-II and naloxone). Each group contain 5 animals (mice). All groups was induced with pyridoxine 400 mg/kg BW i.p for 14 days to cause neuropathy and followed by hyperalgesia, allodynia, and wire-hang test. In the acute toxicity study, we had 1 group and contain 5 animals (rats). The results of the hyperalgesia and allodynia study showed the effect of AC-II was better than AC-I. The combination of pregabalin and AC-II was better than AC-II as monotherapy (p<0.05). However, AC II activity was abolished when combined with naloxone. In wire hang test demonstrated no difference between falling score (p: 0.053) and reaching score (0.903), that showed AC-II wasn’t impaired the motoric system. No death or toxicity symptoms were observed for 14 days in the acute toxicity study. A. conyzoides aqueous extract is potential for anti-neuropathic pain..